Voltammetry of Layered Black Phosphorus: Electrochemistry of Multilayer Phosphorene. Issue 3 (6th February 2015) - Wang, Lu; Sofer, Zdenek; Pumera, Martin
Abstract The front cover artwork is provided by Pumera's group at Nanyang Technological University, Singapore and Sofer's group at UCT, Prague. The image shows the structure of black phosphorus on a backdrop of White Sands National Monument, New Mexico, USA. Find out what this unique design represents by reading the Communication at 10.1002/celc.201402363.